Nephroprotective effects of Foeniculum vulgare mill (Apiaceae Family) hydromethanol leaf extract against cisplatin-induced nephrotoxicity on Swiss albino mice - Kibur Hunie Tesfa; Chernet Desalegn Gebeyehu; Tiget Ayelgn Mengstie; Hiwot Tezera Endale (Phytomedicine Plus)
Background: Cisplatin-induced kidney damage is one of the causes of acute kidney injury that increases morbidity. Therefore, it is mandatory to seek effective, affordable, and safe drugs for the prevention and curative effects of kidney toxicity caused by cisplatin. Thus, this study evaluated the effects of Foeniculum vulgare Mill hydro-methanolic crude leaf extract on cisplatin-induced nephrotoxicity in Swiss albino mice. Methods: The study was conducted on 36 male Swiss albino mice divided into 6 groups (6 mice per group. Group I received distilled water only. Group II was cisplatin control. Group III-V were treated with 100, 200, and 400 mg/kg Foeniculum vulgare Mill respectively. Group VI was treated with 100 mg/kg of silymarin. Group II-VI was administered a single dose of 7.5 mg/kg cisplatin on the 11th day. The mice were anesthetized on the 16th day following the final treatment. Subsequently, kidney function tests and histopathological examination were conducted. Results: Mice that received cisplatin alone (group II) exhibited a significant decrease in body weight on day 16, an increase in serum kidney markers, a decrease in serum sodium and chloride, an increase in potassium and calcium, an increase in relative kidney weight, and pathological damage to the kidney as compared to the normal control group. The group of mice treated with 200 mg/kg, 400mg/kg of extract, and silymarin control significantly reduced the serum kidney markers and prevented pathological damage to the kidney compared to the negative control group. Conclusion: The present study's findings revealed that Foeniculum vulgare Mill exhibits nephroprotective activities by ameliorating nephrotoxicity in a dose-dependent manner.